Hydromechanical interactions in a fractured carbonate reservoir inferred from hydraulic and mechanical measurements - Cappa, F.; Guglielmi, Y.; Fénart, P.; Merrien-Soukatchoff, V.; Thoraval, A. (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2005)
Hydromechanical coupled processes in a shallow fractured carbonate reservoir rock were investigated through field experiments coupled with analytical and numerical analyses. The experiments consist of hydraulic loading/unloading of a water reservoir in which fluid flow occurs mainly inside a heterogeneous fracture network made up of vertical faults and bedding planes. Hydromechanical response of the reservoir was measured using six pressure–normal displacement sensors located on discontinuities and two surface tiltmeters. A dual hydraulic behavior was characterized for low-permeability bedding planes well connected to high-permeability faults. Displacement responses show high-variability, nonlinear changes, sometimes with high-frequency oscillations, and a large scattering of magnitudes. Initial normal stiffnesses and effective normal stresses along fault planes were estimated in the field by interpreting pressure–normal displacement relations with a nonlinear function between effective normal stress and normal displacement. Two-dimensional discontinuum modeling with transient fluid flow was performed to fit measurements during hydraulic loading tests. Results show that the hydromechanical behavior of the reservoir is restored if a high stiffness contrast is allocated between low- and high-permeability discontinuities. Thus, a dual-permeability network of discontinuities will likely also be a contrasting stiffness network, in which the deformation of major flow-conducting discontinuities is significantly influenced by the stiffness of the surrounding less-permeable discontinuities.